A risk-based tool to support the inspection management in chemical plants. (May 2016) - Vianello, Chiara; Milazzo, Maria Francesca; Guerrini, Ludovica; Mura, Alberto; Maschio, Giuseppe
Abstract: The Risk Based Inspection (RBI), proposed by the American Petroleum Institute, is actually the highest benefit maintenance guidelines in the chemical industry, but data collection that characterises this analysis is very complex and time-consuming. The support of the RBI module of the Inspection Manager software helps in overcoming such issues as it encloses all functionalities for an easier management of technical data in the Plant's Inspection. The objective of this work is to test the newer version of the RBI module, to achieve this aim some quantitative examples were examined. In addition, by means of the support of such a module, results of the consequence assessment were also compared with those obtained by two commercial softwares in order to verify the Inspection Manager 's support in risk-based decisions also when methods for frequency and consequence assessment, different than those of API RBI, are applied and to comment about the available approaches for the consequence analysis. Highlights: Risk-based inspection analysis. Frequency and consequence assessment. Safety management.